1/ \(B=\frac{2x^2-5x+4}{x^2-2x+1}=\frac{2x^2-5x+4}{\left(x-1\right)^2}\)
Đặt \(y=x-1\Rightarrow x=y+1\) thay vào B
\(B=\frac{2\left(y+1\right)^2-5\left(y+1\right)+4}{y^2}=\frac{2y^2-y+1}{y^2}=\frac{1}{y^2}-\frac{1}{y}+2=\left(\frac{1}{y}-\frac{1}{2}\right)^2+\frac{7}{4}\ge\frac{7}{4}\)
Đẳng thức xảy ra khi y = 2 <=> x = 3
Vậy min B = 7/4 khi x = 3
2/ \(C=\frac{x^2-6x+6}{x^2-2x+1}=\frac{x^2-6x+6}{\left(x-1\right)^2}\)
Tới đây bạn làm tương tự 1/
3/ \(D=\left(x-2\right)\left(x-3\right)=x^2-5x+6=\left(x-\frac{5}{2}\right)^2-\frac{1}{4}\ge-\frac{1}{4}\)
min D = -1/4 khi x = 5/2
Tìm min của B= /2x+1/ + /2x-5/
P/s mk đnag cần gấp